AVALIAÇÃO DO EFEITO DA CURCUMINA SOBRE A TOXICIDADE DA ANFOTERICINA B - Voncik, Ketlyn Simone (2014)
Amphotericin B is a macrolide antibiotic used against systemic fungal infections and leishmaniasis. Due to the increasing number of immunocompromised patients and resistance to antimicrobial drugs Amphotericin is in focus, even though the drug discovery in 1955 has been used effectively with little fungal resistance. The drug has hepatic, hematologic and renal toxicity, and its use is often necessary to discontinue. Curcumin is a natural pigment that has been used in conjunction with nephrotoxic and hepatotoxic drugs, mitigating their effects. Three experiment that aimed to determine the dose and timing of administration of Amphotericin B nephrotoxicity, hepato-and hematotoxicity and check the action of Curcumin on the toxicity of the drug were performed in addition to the possible changes caused by the use of curcumin in the biochemical, hematological and histopathological parameters. The initial experiment was a curve of dose and time of administration of Amphotericin B ( 20 mg/kg/10 days , 40 mg/kg/10 days , 80 mg/kg/10 days , 20 mg/kg/30 days , 40 mg / kg/30 days, n = 6 ) to determine the toxic dose . The second experiment consisted in the application of Amphotericin B intravenously (3 mg / kg) and oral administration of Curcumin (100 mg / kg) for 5 days (n=8). The third experiment involved the intravenous administration of Amphotericin B deoxycholate (1 mg / kg) and curcumin (100 mg / kg ) for 5 days (n = 10). To check hematological changes of animals were performed. Renal function was assessed by measurement of urea and serum creatinine and liver function by quantifying the ALT and alkaline phosphatase. Histopathological examination of kidneys and livers of animals were performed. The results were expressed as mean and standard deviation and the adopted significance level of 5 %. Were employed statistic test Shapiro -Wilk and Levene test for homogeneity of variances of the groups. For variables that did not violate the assumption of homogeneity was employed one-way ANOVA and post hoc Bonferroni and the variables who violated was used the nonparametric test Kruskal- Wallis with a significance value correction for multiple comparisons, followed by test Dunnet. In Curve dose changes occurred in hematological parameters, compared to the control groups in 40 mg/kg/10 days and 80 mg/kg/10 days. In the second experiment, Amphotericin B group of all groups differed with respect to urea. In the third experiment infusion reactions were observed in animals in which it was applied to Amphotericin B deoxycholate, occurring death in 50 % of animals treated with Amphotericin B deoxycholate and 30% treated concomitantly with amphotericin B deoxycholate and Curcumin. There are indications of protective pigment on acute drug reactions, however this experiment we observed changes in hematological parameters (hematocrit, hemoglobin and number of red blood cells) in animals treated with amphotericin B deoxycholate and Curcumin / curcumin when compared with those of group control, a fact that was not observed in the previous experiment. So it has not been possible to check liver and kidney toxicity of Amphotericin B and the protective action of curcumin. It can be stated that curcumin did not cause hepatic and renal changes as well as weight of the animals. This new form studies should be conducted to verify the activity of Curcumin on infusion reactions of Amphotericin B deoxycholate and possible hematological changes caused by natural compound.